2018
DOI: 10.15408/es.v10i2.8021
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy of Metacognition to Improve Problem Solving Competency in Kinetic Theory of Gases

Abstract: This is an open access article under CC-BY-SA license Tersedia online di EDUSAINS Website: http://journal.uinjkt.ac.id/index.php/edusains EDUSAINS, 10 (2), 2018, 265 -274 Research Artikel STRATEGI METAKOGNISI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI TEORI KINETIK GASAbstract Metacognition is the most important part of problem solving, in which students control consciously the cognition activity in planning, monitoring and evaluating the physics problem solving. The purpose of this research is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…With scientific literacy, students will be able to learn further and live in a modern society which is currently heavily influenced by developments in science and technology (Bussi, et al, 2012). In addition, with scientific literacy, students are expected to have sensitivity in solving global problems such as environmental, health and economic problems (Carson, 2007;Himawan & Winarti, 2018;Osborne, et al, 2003;Pratiwi, et al, 2019;Yerushalmi & Eylon, 2004). This is because understanding science offers a solution to these problems.…”
Section: Figure 5 Scientific Literacy Model Of Gräbermentioning
confidence: 99%
“…With scientific literacy, students will be able to learn further and live in a modern society which is currently heavily influenced by developments in science and technology (Bussi, et al, 2012). In addition, with scientific literacy, students are expected to have sensitivity in solving global problems such as environmental, health and economic problems (Carson, 2007;Himawan & Winarti, 2018;Osborne, et al, 2003;Pratiwi, et al, 2019;Yerushalmi & Eylon, 2004). This is because understanding science offers a solution to these problems.…”
Section: Figure 5 Scientific Literacy Model Of Gräbermentioning
confidence: 99%
“…The results of Mahen & Nuryanti (2018) research show that as many as 82.9% of research subjects are categorized as low in understanding the concept of simple harmonic vibrations. Himawan & Winarti (2018) found that the standard of material mastery depended on problem-solving skills. Therefore, integrating problem solving related to everyday life is needed in teaching the concept of simple harmonic vibrations, so that students better understand the concept.…”
Section: Introductionmentioning
confidence: 99%